Mobilizing Deposits; the role of Commercial Banks in Ghana - Opoku, Sylvester (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Commonwealth Executive Masters in Business Administration, October, 2011